Tactile sensory and pain thresholds in the face and tongue of subjects asymptomatic for oro‐facial pain and headache. (19th July 2014) - Okayasu, I.; Komiyama, O.; Ayuse, T.; De Laat, A.
Summary The aim of this study was to examine the tactile sensory and pain thresholds in the face, tongue, hand and finger of subjects asymptomatic for pain. Sixteen healthy volunteers (eight men and eight women, mean age 35·7 years, range 27–41) participated. Using Semmes–Weinstein monofilaments, the tactile detection threshold (TDT) and the filament‐prick pain detection threshold (FPT) were measured at five sites: on the cheek skin (CS), tongue tip (TT), palm side of the thenar skin (TS), dorsum of the hand (DH) and the finger tip (FT). The difference between the tactile sensory and pain threshold (FPT–TDT) was also calculated. Both for the TDT and FPT, TT and DH had the lowest and highest values, respectively. As for the FPT–TDT, there were no significant differences among the measurement sites. As the difference between FPT and TDT (FPT–TDT) is known to be an important consideration in interpreting QST (quantitative sensory testing) data and can be altered by neuropathology, taking the FPT–TDT as a new parameter in addition to the TDT and FPT separately would be useful for case–control studies on oro‐facial pain patients with trigeminal neuralgia, atypical facial pain/atypical odontalgia and burning mouth syndrome/glossodynia.